Prevalencia de factores de riesgo asociados a trastornos del comportamiento alimentario en adolescentes de una institución educativa en Cali, Colombia 2005 (2008)
Introduction: eating disorders (ED) are topics of current interest for clinical, epidemiological and basic research. This study was aimed at determining the prevalence and perceptions of risk associated with ED in female adolescents from an educational Institution in the city of Cali. Materials and methods: an observational, cross-sectional study was carried out with a sample of teenagers from an educational institution in Cali, Colombia. A questionnaire was designed and validated for collecting data. Univariate and bivariate analyses were performed using 95% confidence intervals and a P <0.05 significance level. Individual, family and social behavior was reported. Results: students' average age was 13; 7.1% of them (3.5%-10.7% 95%CI) cited vomiting as a way of losing weight. Their relatives identified 86.9% (82.2%-86.9% 95% CI) of them using laxatives to lose weight while friends and peers reported 15.7% (10.6%-20.8% 95%CI) inducing vomiting and seeing 12.6% (8.0%-17.2% 95%CI) of them using diet pills. There was 3.5% prevalence of risk of ED, this being statistically significant in those aged more than 15 and in girls from the ninth grade and above (P <0.05). Discussion: although the prevalence of risk found in this research was low in relation to others, it can be partly attributed to methodological reasons or these adolescents' average age, as they were younger than in other studies.